The Courage of Doing Philosophy : Essays Presented to Leszek Nowak. - Brzezinski, Jerzy. (Rodopi Religion, Theology and Philosophy Special E-Book Collection, 2007-2014, ISBN: 9789004357938., 2007)
In recent years, the problem if idealization has been one of the central issues discussed in philosophy of science. This volume gathers original essays written by well-known philosophers. The papers address the method of idealization and its applications in science as well as ontological and epistemological problems that have arisen. Among the questions addressed are: What is the logical form of idealizational statements and how should they be interpreted? Is the possible worlds semantics useful in understanding idealization? What is the relation between idealization and truth? The volume is a celebration of Leszek Nowak's sixtieth birthday.